2021
DOI: 10.26552/com.c.2021.3.a184-a192
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Infrastructure Spending on Economic Growth: A Case Study of Indonesia

Abstract: This paper aims to analyze the impact of infrastructure spending on economic growth in Indonesia, which includes investment in road, port and irrigation infrastructure. The period of observation was 2011-2018, which covered 29 provinces with consideration of data availability. This study employed the growth model with a panel data analysis, which analyze the relationship between the economic growth and government investment in infrastructure in the long run. The most essential finding in this study is that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…While according to Rutherford (2012), infrastructure is the main service of a country that allows economic and social activities to occur by providing transportation, public health services, educational services and buildings for community purposes. Other scholars define infrastructure as a physical system which produces transportation, irrigation, drainage, buildings and other public facilities to meet human basic needs in the social and economic sphere (Kodoatie, 2005;Syadullah & Setyawan, 2021). Furthermore, Pranessy et al (2012) explained that infrastructure is an important input for production activities and it can affect the economy in various ways, either directly or indirectly.…”
Section: Infrastructuresmentioning
confidence: 99%
“…While according to Rutherford (2012), infrastructure is the main service of a country that allows economic and social activities to occur by providing transportation, public health services, educational services and buildings for community purposes. Other scholars define infrastructure as a physical system which produces transportation, irrigation, drainage, buildings and other public facilities to meet human basic needs in the social and economic sphere (Kodoatie, 2005;Syadullah & Setyawan, 2021). Furthermore, Pranessy et al (2012) explained that infrastructure is an important input for production activities and it can affect the economy in various ways, either directly or indirectly.…”
Section: Infrastructuresmentioning
confidence: 99%
“…Road improvements have been shown to increase individual economic activity and boost regional economic growth by facilitating market access and trade [2]. [3] found that infrastructure development, especially road infrastructure, significantly encourages economic growth.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical evidence relating to the effect of government spending on economic growth has been widely obtained from studies carried out in Indonesia. The research in question includes Rifa 'i & Moddilani (2021), Syadullah & Setyawan (2021), Wibowo (2020), Mudiarcana & Marhaeni (2018), Putri, Azwardi, Marwa & Andaiyani (2018), Wahyudi (2020), Prasetyo & Zuhdi (2013). These studies have discussed numerous perspectives and locus.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Rifa 'i & Moddilani (2021) discussed the effect of education spending on economic growth using time series analysis. Syadullah & Setyawan (2021) analysed the impact of infrastructure spending on economic progress, Wibowo (2020) discussed the influence of three main budgets on regional economic growth. Mudiarcana & Marhaeni (2018) only observed the connection between government expenditure on economic development in Balin Province.…”
Section: Introductionmentioning
confidence: 99%